Reakcja mezofauny (Collembola and Acarina) zamieszkująca łąki na mineralnych i organicznych glebach, na wiosenne doświadczalne pożary - Izabella Olejniczak; Stefan Russel; Anna Prędecka (Studia Ecologiae et Bioethicae)
The impact of spring experimental fires on collembolan and mite communities was studied in this field experiment. In April 2008, experimental plots of 1m2 in size were chosen and burnt. Samples were taken just after fire, and 3, 7 and 12 months following the fire, in burnt plots, at the border of burnt plots and in surroundings (control). The impact of spring experimental fire on mesofauna was ambiguous. But it seems that effects of spring fires were more severe in the case of springtails than for mites.